Modeling of Bi-Polar Leader Inception and Propagation from Flying Aircraft Prior to a Lightning Strike - Sayantan Das; Udaya Kumar (Atmosphere, 2022)
Lightning is one of the major environmental threats to aircraft. The lightning strikes during flying are mostly attributed to aircraft-triggered lightning. The first step toward designing suitable protective measures against lightning is identifying the attachment locations. For this purpose, oversimplified approaches are currently employed, which do not represent the associated discharge phenomena. Therefore, in this work, a suitable model is developed for simulating the inception and propagation of bi-polar leader discharge from the aircraft. Modeling of leader discharges requires field computation around the aircraft, which is carried out employing the Surface Charge Simulation Method (SCSM) combined with sub-modeling, which ensures the best accuracy of field computations near nosecone, wingtips, etc. A DC10 aircraft model is considered for the simulation. Simulations are performed for different pairs of leader inception points on aircraft using the developed model. Subsequently, corresponding ambient fields required for stable bi-polar discharge from aircraft are determined. These values are in the range of measured ambient fields reported in the literature. In summary, the present work has come up with a suitable model for simulating the bi-polar leader inception and propagation from the flying aircraft. Using the same, a detailed quantitative description of the discharge phenomena from the aircraft is provided.